Islam dan Politik Hukum dalam Undang-Undang Nomor 3 Tahun 2022 Tentang Ibu Kota Negara - Ade Andriani; Surya Hady Winata (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This research aims to explain the views of Siyāsah Dustūriyyah, Legal Politics and Benefits regarding the legislation of Law Number 3 of 2022. This type of research is normative juridical research, namely conducting research through legal materials in the broadest sense, usually called library research. ). This research is also descriptive analytical in nature with a normative approach to law enforcement or a law enforcement-based approach (State Approach). The data collection techniques in this research were carried out using literature study and qualitative deductive analysis. The research results show that in the sense of siyāsah dustūriyyah, law number 3 of 2022 already has Islamic principles which do not yet have the principles of shura' and democracy. However, it ignores the role of society in its formation. The Islamic principles applied are the implementation of IKN law through a process of planning, preparation, discussion, determination, dissemination, as well as research and interpretation. Legal Policies and Regulations National Capital Law no. 3 of 2022 does not provide good and fair guidance according to the country's needs. Because the contents of the National Capital Law no. 3 of 2022 is not in accordance with the conditions and needs of the land and people of Indonesia.